(untitled) (Journal of Parents and Teachers, 2019)
There are many places, people and realities of which we don’t know anything. People we don’t care about because they are not in our close circle of friends. Unfair situations we don’t feel responsible for because they are indifferent to us. The idea of global citizenship is achieved by opening ourselves to the meeting, building bonds and relationships with that that doesn’t seem to exist in our daily life. That is the reason why pedagogy of transformative meeting is key to the education in said global citizenship.